2021
DOI: 10.1097/cin.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Applications, Cancer Survivors, and Lifestyle Modification

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
(216 reference statements)
0
4
0
Order By: Relevance
“…We identified that remote-or hybrid-delivered interventions are most likely to meet retention goals. Similar to what has been concluded in previous work, this suggests continued efforts to develop effective programming using web-based and telephone resources [50]. Additionally, studies which reported protocol-specified retention goals and strategies were less likely to see differences in attrition by study arm compared to those that did not report.…”
Section: Discussionsupporting
confidence: 80%
“…We identified that remote-or hybrid-delivered interventions are most likely to meet retention goals. Similar to what has been concluded in previous work, this suggests continued efforts to develop effective programming using web-based and telephone resources [50]. Additionally, studies which reported protocol-specified retention goals and strategies were less likely to see differences in attrition by study arm compared to those that did not report.…”
Section: Discussionsupporting
confidence: 80%
“…The risk of cancer recurrence and the increased risk of chronic diseases brought on by cancer treatments endanger the well-being of cancer survivors ( 52 ). Improving lifestyle behaviors attenuates these risks, and in particular, nutrition and physical activity have been considered powerful allies to cancer patients and survivors, as they positively impact body mass, physical fitness, fatigue, depressive symptoms, anxiety, inflammatory profile, and quality of life ( 53 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the resulting mHealth app to improve public health may be considered an outcome from a design standpoint, but it is not considered a health outcome from a public health standpoint, where the key outcome of interest is the app’s impact on public health [ 27 ]. HCD practice is frequently evaluated through short-term usability testing or short-term feasibility study of design solutions [ 48 ]. However, existing mHealth design literature focuses heavily on short-term behavior changes [ 29 ] and overlooks long-term usage [ 48 ].…”
Section: Gaps In Current Hcd Practice In Achieving Long-term Efficacy...mentioning
confidence: 99%
“…HCD practice is frequently evaluated through short-term usability testing or short-term feasibility study of design solutions [ 48 ]. However, existing mHealth design literature focuses heavily on short-term behavior changes [ 29 ] and overlooks long-term usage [ 48 ]. Based on the anticipated usage of mHealth apps in lifestyle management, disease management, and even self-diagnosis, desired outcomes are unlikely to be achieved with short-term usage.…”
Section: Gaps In Current Hcd Practice In Achieving Long-term Efficacy...mentioning
confidence: 99%